Dartos reflex as autonomic assessment in persons with spinal cord injury - Soler, J. M. (Spinal Cord Ser Cases, 2017)
STUDY DESIGN: Prospective clinical series. OBJECTIVES: The dartos reflex (DR) produces unilateral elevation of the testis with vermicular contraction of the scrotal skin and penile retraction. It is a somato-autonomic reflex that depends on the T11-L2 sympathetic segment. Its presence was analysed in men with various levels and severities of spinal cord injury (SCI). SETTING: France. METHODS: Male patients with SCI undergoing urodynamic or sexual assessment were included. DR of the scrotum and penis were systematically assessed in addition to the usual neurological examination that included assessment of the autonomic system, cremaster, and sacral reflexes. The DR was evoked by applying a small ice pack on the scrotum, separately to each side. RESULTS: Forty-six patients were assessed. DRs were always present when the T11-L2 segment was intact above the lesion (low paraplegia below L2) or below the lesion in an upper motor neuron (UMN) syndrome (spastic paraplegia above T10). They were more pronounced in the case of UMN syndrome. In the case of lower motor neuron (LMN) syndrome that included the T11-L2 segment, DRs disappeared in all but one patient. Patients with a LMN lesion were more prone to retrograde or absent ejaculation, loss of psychogenic erection, and open bladder neck. CONCLUSIONS: The DR is a valuable test for the assessment of the integrity and excitability of the T11-L2 spinal segment. It is easy to perform and is predictive of some aspects of sexual and bladder neck function in men. DR should be considered as an addition to the autonomic standards.